Hydrodynamics of an inverse liquid–solid circulating conventional fluidized bed. Issue 4 (22nd January 2022) - Nan, Tian; Zhu, Jesse
Abstract: An inverse liquid–solid circulating conventional fluidized bed (I‐CCFB) is realized by injecting particles from the top of a conventional liquid–solid fluidized bed (0.076 m ID and 5.4 m height) that is operated in a newly developed circulating conventional fluidization regime located between the conventional and circulating fluidization regimes. The I‐CCFB can achieve a higher solids holdup compared to both conventional and circulating liquid–solid fluidized beds. A new parameter, the bed intensification factor, is defined to quantify the increased solids holdup observed with external solids circulation. The Richardson–Zaki equation is shown to be applicable to the I‐CCFB regime and can be used to correlate the slip velocity and solids holdup, both of which increase with the solids circulation rate. A new flow regime map is presented, including the I‐CCFB and a variety of other liquid–solid fluidized beds.